2014
DOI: 10.1007/s10295-014-1489-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of a stress-minimisation paradigm in high cell density fed-batch Escherichia coli fermentations to optimise recombinant protein production

Abstract: Production of recombinant proteins is an industrially important technique in the biopharmaceutical sector. Many recombinant proteins are problematic to generate in a soluble form in bacteria as they readily form insoluble inclusion bodies. Recombinant protein solubility can be enhanced by minimising stress imposed on bacteria through decreasing growth temperature and the rate of recombinant protein production. In this study, we determined whether these stress-minimisation techniques can be successfully applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 32 publications
7
32
0
Order By: Relevance
“…A and B, it is possible to see that the highest cellular growths do not always result in high production yields of the target‐protein, since, herein, the best condition to produce EGFP (150 rpm) had only the third‐best bacterial growth. In general, the production of EGFP is associated with the amount of viable bacterial cells in culture , but, similarly to the results observed in our study, some previous reports highlighted that high cellular density not always results in an increase in the production of some biomolecules . Previously, Chew et al.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…A and B, it is possible to see that the highest cellular growths do not always result in high production yields of the target‐protein, since, herein, the best condition to produce EGFP (150 rpm) had only the third‐best bacterial growth. In general, the production of EGFP is associated with the amount of viable bacterial cells in culture , but, similarly to the results observed in our study, some previous reports highlighted that high cellular density not always results in an increase in the production of some biomolecules . Previously, Chew et al.…”
Section: Resultssupporting
confidence: 91%
“…Despite attaining the highest EGFP production yields with the induction at the end of the exponential phase, in general, late induction for the expression of recombinant proteins can entail some drawbacks in an industrial process. It can stimulate the synthesis and activity of proteases, impacting the productivity and increasing the contaminants present in the sample . This is particularly relevant for the manufacturing of commercial proteins because it can impair and increase the costs of the following downstream purification stages.…”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated that stress minimization by decreasing culture temperature and inducer concentration can be used to improve not only recombinant protein yields and folding but also correct subcellular targeting and overall cell integrity for subsequent cell harvest and protein release steps . Careful balancing of increases in inducer concentration and decreases in growth and induction temperature allowed optimization of Fab D1.3 yield.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent this problem, plasmid stability is usually ensured by adding an antibiotic to the culture medium while having the corresponding antibiotic resistance gene inserted into the plasmid (23,27,32). Despite being a simple and practical method, particularly for academic research, this system is not without its downsides: it risks spreading antibioticresistance genes to pathogens (23,27,33) and faces decreasing performance over the course of cell culture (33,34). Potential antibiotic-free alternatives for plasmid maintenance are toxin-antitoxin systems, which are based on two genes: one that codes for a lethal toxic protein (the "toxin"), which may be present in the plasmid or the chromosome; and another gene that gives rise to a protein (or a non-coding RNA) that counteracts the toxin (the "antitoxin"), inserted into the plasmid (35)(36)(37)(38)(39).…”
Section: List Of Figuresmentioning
confidence: 99%
“…Plasmid segregational stability in bacterial cultures is usually ensured by inserting an antibiotic resistance gene (such as kanamycin or ampicillin resistance) into the plasmid, and, at the same time, adding the corresponding antibiotic to the culture medium (27,31,37,39); consequently, upon cell division, if a daughter cell receives no plasmid copy from the mother cell, it dies. This method, however, presents some drawbacks for producing recombinant proteins on a large scale, especially the high cost of antibiotics (36,39,179), the risk of spreading antibiotic resistance genes to pathogens through horizontal gene transfer (23,27,33), the decline in performance over the course of cell culture (33,34,39), and, particularly in the case of products for human use, the requirement to remove the antibiotics from the final product (36,39). Thus, some alternative approaches have been developed, which we group here in four broad categories: complementation systems, toxin-antitoxin systems, partitioning systems and chromosomal integration methods.…”
Section: Plasmid Segregational Stability In Bacteriamentioning
confidence: 99%